Barbashin conditions for uniform instability of evolution operators - MEGAN, Mihail; BORUGA (TOMA), Rovana (Studia Universitatis Babeș-Bolyai Mathematica, 2021)
The aim of the present paper is to give some characterization theorems of Barbashin type for the uniform exponential instability and uniform polynomial instability behavior of evolution operators. Also, some examples which illustrate the connections between the concepts presented are given. Mathematics Subject Classification (2010): 47B01, 34D05.